A substituent effect of phenylacetic acid coligand perturbed structures and magnetic properties observed in two triple-bridged azido-Cu(ii) chain compounds with ferromagnetic ordering and slow magnetic relaxation. Issue 23 (2nd June 2017) - Liu, Xiangyu; Ma, Xiaohui; Cen, Peipei; Wu, Yuewei; Zhang, Chengcheng; Shi, Quan; Song, Weiming; Xie, Gang; Chen, Sanping
Abstract : Two triple-bridged azido-Cu(ii ) chains exhibit distinct magnetic behaviors. Abstract : Based on two fluoro-substituted phenylacetate isomers, o -fluorophenylacetic acid ( o -Hfpa) and p -fluorophenylacetic acid ( p -Hfpa), two new Cu(ii )-azido compounds, [Cu( o -fpa)(N3 )(C2 H5 OH)] n (1 ) and [Cu( p -fpa)(N3 )(C2 H5 OH)] n (2 ), have been prepared, and structurally and magnetically characterized. Single-crystal structure analyses indicate that compounds1 and2 consist of 1D chain-like coordination networks in which adjacent copper cations are linked by the alternating triple-bridges of μ-1, 1-azido, syn, syn -carboxylate and μ2-ethanol. For the two title compounds, the diverse charge distributions on the carboxyl groups caused by distinct substituent effects of the two phenylacetate coligands lead to the different structural parameters of intrachain Cu–Cu distances (3.218 Å for1 and 3.168 Å for2 ) and Cu–N–Cu angles (106.82° for1 and 104.81° for2 ), further resulting in the disparity of magnetic behaviors. The dominant ferromagnetic couplings between neighbouring Cu(ii ) ions in the two compounds ( J = 87.08 cm −1 for1, J = 66.05 cm −1 for2 ) are due to the counter-complementarity of the multiple superexchange pathways, contributing to the interesting plots of a ferromagnetic order ( T c = 11.0 K for1, 9.5 K for2 ) and slow magnetic relaxation that are rarely observed in most of the reported azido-Cu(ii ) architectures. Heat-capacity experiments further emphasize the characteristic long-range ferromagnetic ordering in compounds1 and2 . Magneto-structural relationships of1 and2 are investigated as well. Moreover, DFT calculations (using different methods and basis sets) have been performed on both compounds to provide a qualitative and quantitative theoretical explanation of their magnetic behavior.